Carex secalina (Cyperaceae), a critically endangered species of Europe: historic and new localities in Poland - Marlena Lembicz; Agnieszka Bogdanowicz; Julian Chmiel; Waldemar Żukowski (Acta Societatis Botanicorum Poloniae, 2011)
Carex secalina, a species recognized as extinct in Poland for 40 years, was re-discovered in 2000 and it’s natural populations covered by monitoring. From among nine historic localities, only for two - Jacewo and Turzany, in the vicinity of Inowrocław - the occurrence of the species was confirmed. In the course of the field studies, six new localities, not previously recorded in literature, were discovered. The sedge occupies sub-halophytic habitats in which it occurs along with halophytic species (particularly, such as Glaux maritima and Pucinellia distans) and a group of ruderal taxons. One of the newly discovered localities of C. secalina comprises an anthropogenic habitat. On the whole, the population sizes ranged from 20 to 350 individuals. The studies revealed a positive correlation between the size of a population and cattle pasturing, i.e. C. secalina forms the largest populations in the habitats remaining under the intense pressure of grazing and treading. Moreover, it was found that the high generative reproduction rate compensates the damage caused by animal grazing. The results suggest that an active protection of the sedge populations through the agricultural use of its habitats is the only effective way of securing it’s further occurrence in Poland, while including the sub-halophytic pastures with C. secalina in the agricultural and environmental program should be a priority task in the nearest future.